Helping Mothers Survive Bleeding After Birth: An Evaluation of Simulation-based Training in a Low-Resource Setting. Issue 3 (September 2015) - Nelissen, E.; Ersdal, H.; Østergaard, D.; Mduma, E.; Broerse, J.; Evjen-Olsen, B.; Van Roosmalen, J.; Stekelenburg, J.
Abstract : ( Acta Obstet Gynecol Scand . 2014;93:287–295)